Visibility and impact of the microcredit and the digital social media: A case study of financial institutions in Ecuador - Salas Tenesaca, E. (2017)
This study analyses the impact and visibility of financial institutions that promote the microcredit product through digital social media such as Facebook and Twitter in Ecuador. It analyses 70 Ecuadorian financial institutions that according to data from the Ecuadorian Superintendence of Banking and Insurance and the Ecuadorian Superintendence of Popular and Solidary Economy, until July of 2015, they offer the microcredit within their portfolio of products. The registered information in Facebook and Twitter was gathered by using: Netvizz, Followerwonk, Klear, Twitalyzer and Twopcharts; from which, it analyses the number of publications, type of publications, among other elements. It concludes that digital social media sites such as Facebook and Twitter have a great amount of users within the Ecuadorian financial system; however, the activity generated by the financial institutions is very limited. The visibility of micro-credits in these digital social media is very low. The existing information as well as the use of multimedia elements is minimum. © Springer International Publishing Switzerland 2017.